2009
DOI: 10.1007/s11882-009-0023-4
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin sensitivity and desensitization for asthma and sinusitis

Abstract: NSAIDs-including aspirin (ASA)-that inhibit cyclooxygenase (COX)-1 induce nonallergic hypersensitivity reactions consisting of attacks of rhinitis and asthma. Such reactions occur exclusively in a subset of asthmatic patients who also have underlying nasal polyps and chronic hyperplastic eosinophilic sinusitis. We now refer to their underlying inflammatory disease of the entire respiratory tract as aspirin-exacerbated respiratory disease. This review focuses on descriptions of these patients; methods available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 49 publications
1
71
0
9
Order By: Relevance
“…The NSAID sensitivity often manifests as ASA intolerance, and the disorder is now generally referred to as aspirin (or NSAID)-exacerbated respiratory disease (AERD). [947][948][949] Prevalence rates of AERD in the general population have been estimated at 0.6% to 2.5% and in CRSwNP patients at 9.7%. 950,951 An incomplete triad might be observed in patients with recurrent nasal polyposis and asthma who do not yet report adverse reactions to NSAIDs.…”
Section: Viiic1h Crswnp Pathophysiologymentioning
confidence: 99%
“…The NSAID sensitivity often manifests as ASA intolerance, and the disorder is now generally referred to as aspirin (or NSAID)-exacerbated respiratory disease (AERD). [947][948][949] Prevalence rates of AERD in the general population have been estimated at 0.6% to 2.5% and in CRSwNP patients at 9.7%. 950,951 An incomplete triad might be observed in patients with recurrent nasal polyposis and asthma who do not yet report adverse reactions to NSAIDs.…”
Section: Viiic1h Crswnp Pathophysiologymentioning
confidence: 99%
“…8,9 Nasal therapy with increasing doses of lysine aspirin following a positive nasal challenge has been used in our department for several years. 10 Most patients can reach a total dose equivalent to 60-75mg aspirin in the nose, with benefit in the majority and a better safety profile than with oral aspirin.…”
Section: Desensitisationmentioning
confidence: 99%
“…The central mechanism was regarded as the deprivation of PGE 2 as a consequence of COX-1 inhibition, which would lead to an even more increased local and systemic generation of cysteinyl leukotrienes (LT). The overproduction of cysteinyl LT, due to upregulation of LTC 4 synthase and/or cysteinyl LT receptors in the airways, the hallmark of the disease, occurs at baseline as well, although at a much lower degree than after aspirin/NSAIDs intake [2].After the introduction of the selective COX-2 inhibitors, casually referred to as coxibs, several well-designed studies reported the excellent safety profile of these new NSAIDs in patients with AERD [3,4]. Nevertheless, shortly afterwards, as the use of coxibs extended, so did the number of case reports warning the clinicians that some AERD patients may not tolerate coxibs [5,6].…”
mentioning
confidence: 99%
“…The central mechanism was regarded as the deprivation of PGE 2 as a consequence of COX-1 inhibition, which would lead to an even more increased local and systemic generation of cysteinyl leukotrienes (LT). The overproduction of cysteinyl LT, due to upregulation of LTC 4 synthase and/or cysteinyl LT receptors in the airways, the hallmark of the disease, occurs at baseline as well, although at a much lower degree than after aspirin/NSAIDs intake [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation